Microstructure and texture evolution during multi-direction forging of titanium. (2021) - Chouhan, Devesh Kumar; Biswas, Somjeet
Abstract: Wrought Titanium is used as load-bearing aircraft and automobile components due to superior specific strength, low density, and corrosion resistance. In this work, Titanium billets were subjected to open-die forging successively along mutually perpendicular axes at ambient temperature. Microstructure and texture evolution was investigated using optical microscopy and electron backscattered diffraction in a scanning electron microscope to understand deformation behaviour. The analysis revealed (i) the grain refinement through dislocation activities with the increase in geometrically necessary dislocations, (ii) evolution and interaction of considerable 10 1 - 2 extension and 11 2 - 2 contraction twins leading to the formation of coincident site lattice boundaries, and (iii) unusual but desirable texture. Strength of the material improved considerably after the ambient temperature multi-direction forging.